Methods in Applied Ethology: Determining baseline activity of pigs in individually housed laboratory environment - Ruiz, Maria A.; Schmitz, Ashley N.; Luo, Yunzhi; Hulbert, Lindsey E. (My University, 2016)
The objective of this undergraduate research was to become familiarized with methods and technology used in applied ethology. Applied ethology researches practical issues for the care of domestic animals (Price, 2008). The focus in my undergraduate research was to observe oral-nasal-facial (ONF) behavior of Yucatan miniswine boars in a laboratory environment, with 12-hour light and 12-hour dark artificial lighting. ONF is defined with rubbing, sniffing, licking, biting, and touching the mouth, snout, or face to an external object; ONF is a nonfeeding behavior in that no feed was present when ONF was recorded (Hulbert, 2006). ONF behaviors in normal pigs have a circadian rhythm, meaning an endogenously controlled 24-hour cycle of activity (Price, 2008). Daily ONF duration can serve as a baseline to pigs showing abnormal oral behaviors. The pigs were provided the following: housed individually in 190cm X 112cm pens, fed pellet feed twice a day, provided a toy, ad libitum water from a nipple waterer or water bucket. Behaviors were recorded from 7am-7pm (when lights were on) by IP cameras (Dome 3.0 Megapixel 2.8-12mm Lens, GeoVision Inc., Taipei, Taiwan) mounted 2m high from the floor. Each camera provided a bird’s eye view of two pens. Footages were recorded onto a surveillance system (GeoVision, GV-1480 16-Channel PC, DVR, GeoVision Inc.). 12-hour videos were divided into two-hour observation periods, and behaviors were coded with Observer XT 11.5 (Noldus, Lessburg, VA). Three trained students observed 84 videos with 168 hours of footage. We collected data from nine pigs but data from six pigs are presented. ONF behavior was higher than 50% during total observation. There was less ONF around feeding time, (65%, 7-9am & 1-3pm), while more ONF after feeding times (78%, 9-1pm & 3-7pm). Continued observations are underway with longer observation time and more pigs to determine if ONF activity can continue to be used as a baseline behavior for future research.
Keywords: Fall 2016